Identification of Hub Genes in the Pathogenesis of Bronchiolitis Obliterans via Bioinformatic Analysis and Experimental Verification - Wu Z; Chen X; Zhang K; Liu Z; Zhang H; Zheng Z; Zhang X; Chen Y; Peng Y; Li H; Huang K; Tang S; et al. (Dove Medical Press, 2023)
Zhongji Wu,1,* Xiaowen Chen,1,* Kangkang Zhang,1 Zhenwei Liu,1 Haidi Zhang,1 Zhaocong Zheng,2 Xiaodie Zhang,2 Yubiao Chen,3 Yinghui Peng,1 Hui Li,1 Kaiyin Huang,1 Sixiang Tang,1 Li Zhao,1 Dehui Chen1 1The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510000, People's Republic of China; 2Guangzhou Medical University, Guangzhou, 510000, People's Republic of China; 3State Key Laboratory of Respiratory Diseases, Guangzhou, 510000, People's Republic of China*These authors contributed equally to this workCorrespondence: Dehui Chen, 151 Yanjiang West Road, Yuexiu District, Guangzhou City, Guangdong Province, 510000, People's Republic of China, Tel +86 13922732810, Email dehuichen84@126.comBackground: Bronchiolitis obliterans (BO) is a chronic disease that can arise as a complication of severe childhood pneumonia and can also impact the long-term survival of patients after lung transplantation. However, the precise molecular mechanism underlying BO remains unclear. We aimed to identify BO-associated hub genes and their molecular mechanisms.Methods: BO-associated transcriptome datasets (GSE52761, GSE137169, and GSE94557) were downloaded from the Gene Expression Omnibus (GEO) database to identify differentially expressed genes (DEGs). Additional bioinformatics analyses, such as Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Protein-Protein Interaction (PPI) analyses, were performed to determine functional roles and DEG-associated regulatory networks. Prediction of hub genes using the 12 algorithms available in the Cytohubba plugin of Cytoscape software was also performed. Verification was performed using the BO mouse model.Results: Our results revealed 57 DEGs associated with BO, of which 18 were down-regulated and 39 were up-regulated. The Cytohubba plugin data further narrowed down the 57 DEGs into 9 prominent hub genes (CCR2, CD1D, GM2A, TFEC, MPEG1, CTSS, GPNMB, BIRC2, and CTSZ). Genes such as CCR2, TFEC, MPEG1, CTSS, and CTSZ were dysregulated in 2,3-butanedione-induced BO mice, whereas TFEC, CTSS, and CTSZ were dysregulated in nitric acid-induced BO mouse models.Conclusion: Our study identified and validated four novel BO biomarkers, which may allow further investigation into the development of distinct BO diagnostic markers and novel therapeutic avenues.Keywords: bronchiolitis obliterans, biomarkers, pathways, transcriptome, therapeutic targets